A corrupção governamental nos municípios do Ceará nos anos de 2002 a 2011: construção de indicadores e análise - Sousa, Mateus de Carvalho (2018)
The subject studied in this study is government corruption, with the general objective of measuring it in the municipalities of Ceará from 2002 to 2011 through objective indicators and the construction of an indicator of municipal government corruption. The study was carried out in 180 cities in Ceará, with the municipalities of Alcântaras, Chaval, Fortaleza and Reriutaba being withdrawn from the survey because the amounts of the budget paid were not available in the years 2002 to 2004, 2004, 2003 and 2004 The main research on corruption measurement is based on indirect measures and subjective criteria, as well as providing a single indicator for the whole country, without taking into account regional differences. Thus, there are questions about both the methodology of these works and the question of whether this phenomenon occurs uniformly throughout Brazil. Based on the methodology used by Boll (2010) to obtain government corruption in the Brazilian states, and using the data of judgments of irregular accounts, applied debits and budgets of the municipalities of Ceará, made available by the Court of Audit of the State of Ceará - TCE / CE, together with socioeconomic information (population and municipal GDP), objective indicators were generated, which make it possible to better understand the behavior of corruption in the municipalities of the State of Ceará. It was verified that this phenomenon does not occur in a homogeneous way in the municipalities of the State of Ceará, in compliance with the Precepts of the Perceived Corruption Index of Transparency International. With the data obtained, a ranking was made and it was verified that the highest average values of the Municipal Corruption Indicator were presented by Juazeiro do Norte, Caucaia and Santana do Acaraú, while the smaller ones by Ipueiras, Varjota and Catarina. These indicators on government corruption can be used for academic studies in related areas, as well as the availability of this information to public spending control agencies so that they can develop localized actions to reduce the embezzlement of public resources. In addition to being another objective instrument available for citizens to assess the management of their municipalities.